Traffic Evaluation of Traffic Engineering in Underpass Development - Hendrialdi; Josefhine Debora Putri (Jurnal Teknologi Transportasi dan Logistik, 2020)
The density of vehicles that occurred in Simpang Matraman Salemba, due to the high volume of traffic that the delay in APILL not be able to accommodate the entire volume of traffic flowing through Simpang Matraman- Salemba. Thus while the plan drafted by the Department of Highways namely Jakarta Underpass Construction of Matraman-Salemba. Underpass construction plan-Salemba Matraman is located at the intersection of Jalan Matraman Raya gathering, Jalan Matraman, and Jalan Pramuka - Central Jakarta, which would lead to changes in the characteristics of the traffic from the construction process until after the operation of the underpass. Matraman-Salemba Underpass construction carried out by the Highways Department of the Government of Jakarta located at the intersection of Jalan Matraman Raya gathering, Jalan Matraman, and Jalan Pramuka - Central Jakarta. This study aims to determine the traffic engineering in the construction of underpasses Matraman-Salemba, Central Jakarta, evaluate traffic engineering in the construction of underpasses Matraman-Salemba, Central Jakarta, giving the recommendations of the evaluation of traffic engineering.